Wage determination in the US airline industry: union power under product market constraints - Barry T. Hirsch (Institute for the Study of Labor (IZA), 2006)
The paper analyzes wages in the U.S. airline industry, focusing on the role of collective bargaining in a changing product market environment. Airline unions have considerable strike threat power, but are constrained by the financial health of carriers. Since airline deregulation, compensation has waxed and waned in response to the industry's economic environment. Airline workers capture sizable rents following good times and provide concessions following lean times. Compensation at legacy carriers has been restructured; it remains to be seen if compensation will continue its long-run movement toward opportunity costs. Evidence from the CPS for 1995-2006 shows that wage premiums for airline industry workers remain, particularly for pilots, with existing premiums almost entirely a union phenomenon. Much of the gap in wage scales between major and mid-size carriers was erased in the mid-2000s concessionary cycle, but these rates remain much higher than rates at regional carriers. Compensation levels at regional carriers may approximate opportunity cost the compensation necessary to attract and retain qualified employees throughout the industry. Because unions retain bargaining power at the major carriers, wages are likely to head upward as carriers' financial health returns. Such wage levels may or may not be sustainable in the inevitable next downturn.
urn:nbn:de:101:1-20090406133
Keywords: 330